PENGOLAHAN CITRA DIGITAL BERBASIS WIRELESS 2.4 GHz DENGAN MEMANFAATKAN ARDUINO UNO REV 3 - Andika Agung Firmansyah; Denny Dermawan (Compiler, 2015)
Digital image processing of a system capable of generating digital image data and software as a medium to display the digital image data that uses radio waves to send data in HEX and convert in the form of images. Linksprite camera which enable to produce the digital image data and utilize the arduino UNO as a controller to send commands to the camera image capture and send the digital image data to the PC. The process of digital image based data transmission by radio waves utilizing the XBee Pro Series 1 . Results of testing the system implemented in the outdoor can take a longer distance when compared with the application of the system in the room . At a distance of 10-250 meters complete the full HEX data transmission and produces good images , with time ranging 2m.29s.39ms-2m.36s.56ms. Distance of 260-450 meters with a time of 2m.05s.02ms - 06ms 2m 01s but the picture quality is not good. At a distance of 500-530 meters with a time of 1m.10s.23ms-0m.50s.59ms produce images that are very less. While the distance of > 550 meters is the limit HEX data transmission capability to the receiver. The ability of the system mileage in the process of data transfer shorter if applied indoors. Distance of 1-60 meters with a time of 2m.29s.39ms - 60ms.2m.34s produce good quality images. At a distance of 80 meters with a time of 1m.25s.59ms produce poor images, and with a distance of 90 meters with a time 0m.35s.49ms produce images that are very less . While the distance of > 100 system not able to perform HEX data transmission